2017
DOI: 10.1007/s11239-017-1495-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the FXa inhibitors Rivaroxaban and Apixaban on platelet activation in patients with atrial fibrillation

Abstract: Rivaroxaban and Apixaban, increasingly used for stroke prevention in non-valvular atrial fibrillation (AF), might impact platelet reactivity directly or indirectly. By inhibition of Factor Xa (FXa) they preclude not only generation of relevant thrombin amounts but also block signalling of FXa via protease activated receptors. However, weather FXa-inhibition affects platelet haemostasis remains incompletely known. One hundred and twenty-eight patients with AF on chronic anticoagulation with either Rivaroxaban o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…32,33 HMGB-1 is highly expressed in platelet-rich human coronary artery thrombi 34 and a key mediator of reciprocal communication between platelet and neutrophils, as well as monocytes facilitating formation of prothrombotic neutrophil extracellular traps and production of monocyte-derived tissue factor. 33 We found that P-selectin exposure was not affected by VLD rivaroxaban treatment, findings that are in line with previous studies 35,36 that both found no significant effect of rivaroxaban on platelet P-selectin expression and release. However, in the present study, we could show that platelet surface abundance of HMGB-1 was significantly reduced after treatment with VLD rivaroxaban pointing to a potential effect on thrombo-inflammatory processes triggered by platelets in patients with coronary artery disease.…”
Section: Discussionsupporting
confidence: 91%
“…32,33 HMGB-1 is highly expressed in platelet-rich human coronary artery thrombi 34 and a key mediator of reciprocal communication between platelet and neutrophils, as well as monocytes facilitating formation of prothrombotic neutrophil extracellular traps and production of monocyte-derived tissue factor. 33 We found that P-selectin exposure was not affected by VLD rivaroxaban treatment, findings that are in line with previous studies 35,36 that both found no significant effect of rivaroxaban on platelet P-selectin expression and release. However, in the present study, we could show that platelet surface abundance of HMGB-1 was significantly reduced after treatment with VLD rivaroxaban pointing to a potential effect on thrombo-inflammatory processes triggered by platelets in patients with coronary artery disease.…”
Section: Discussionsupporting
confidence: 91%
“…Even at the very low dose of 2.5 mg b.i.d., rivaroxaban reduced platelet-dependent thrombin generation and coagulation-dependent thrombus-formation in patients treated with aspirin plus P2Y 12 inhibitor, whereas pure platelet-dependent thrombus formation was not affected 14 . Indeed, FXa inhibition appears to have no significant effect on platelets 14 including in response to adenosine diphosphate, collagen, thrombin receptor-activating peptide, or arachidonic acid 15 . Apixaban may therefore favourably enhance endogenous fibrinolysis through reduction in platelet-dependent and non-platelet-dependent thrombin generation, which directly impact on the structure and stability of the thrombus and its resistance to fibrinolysis.…”
Section: Discussionmentioning
confidence: 92%
“…However, its activity might be affected with strong induction/inhibition of CYP enzymes or due to severe reduction of the kidney functions [39]. Rivaroxaban probably does not affect platelet aggregation [41, 42]. Several previously published studies [4345] pointed on the fact that diabetes modulates the activity of CYP enzymes; hence, this modulation can, in theory, lead to changed rivaroxaban activity in T2D subjects.…”
Section: T2d and Long-term Rivaroxaban Therapy For Afmentioning
confidence: 99%